PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, KOMPETENSI GURU DAN IKLIM ORGANISASI SEKOLAH TERHADAP KINERJA GURU SEKOLAH MENENGAH ATAS (SMA) NEGERI DI KABUPATEN KULON PROGO TAHUN AJARAN 2012/2013 (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
The Influence of Principal‟s Leadership, the Teachers Competence, and the Organizational School Climate on the Performance of the Senior High School Teacher‟s in Kulon Progo Regency. This study was aims to determine : (1) the influence of the principal‟s leadership, the teachers competence, and the organizational climate school simultanously on the performance of the teachers; (2) the influence of the principal‟s leadership on the performance of the teachers; (3) the influence of the the teachers competence on the performance of the teachers; (4) the influence of the organizational school climate on the performance of the teachers.The study was conducted in Kulon Progo Regency.This research is a quantitative one using survey method. The population of this research was 380 Senior High School teachers in the Kulon Progo Regency. The sample of the research was 177 teachers and was taken by using proportional random sampling technique. The data was collected by using questionnaires. Major hypothesis testing used double regression analysis, and then individual hypothesis testing done by using partial correlation analysis. The data processing used SPSS program 16.0. All effective contribution was taken from theanalysis result of the value of the determination coefficient multiplied by 100% and the effective contribution partially by multiplying the value of the Standardized Beta Coefficients with Zerro-order Corelations value multiplied by 100 % for each independen variable.The results of the research show that the principal‟s leadership, the teachers competence, and the organizational school climate simultanously have very significant and positive influence on the performance of the teachers. Effective contribution all together is 45,70%. Effective contribution individually of: (1) the principal‟s leadership on the performance of the teachers is 11,34%; (2) the teachers competence on the performance of the teachers is 21,83%; (3) the organizational school climate on the performance of the teachers is 12,52%.